Elektronentransfer(ET)-Verhalten von Fluoreszenzfarbstoffen - untersucht am Beispiel von Perylenbisdicarboximiden und einem Dioxaindenoindendion mit Cyclovoltammetrie mit UV/VIS-Spektroelektrochemie und - Josef Salbeck; Horst Kunkely; Heinz Langhals; Rolf W. Saalfrank; Jörg Daub (CHIMIA)
N,N'-Bis(2,5-di-tert-butylphenyl)-3,4:9,10-perylenebis(dicarboximide) (1a), N,N'-bis(1-hexylheptyl)-3,4:9,10-perylenebis(dicarboximide) (1b), and 1,1,3,3,6,6,8,8- octamethyl-1,2,3,6,7,8-hexahydro-5,10-dioxaindeno[5,4-e]indene-4,9-dione (2) have been used to study the electron-transfer behaviour of fluorescent dyes by cyclovoltammetry and by UV/VIS-spectroelectrochemistry in absorption and emission. Absorption spectra are reported for the ionic species, 1⊙⊖, 12⊖, 1⊙⊕, and 2⊙⊖. Compounds 1 and 2 exhibit distinctive electrochemiluminescent behaviour.